THE EXISTENCE OF INDONESIAN ENGLISH: INDONESIAN SENIOR HIGH SCHOOL ENGLISH LANGUAGE TEACHERS’ VOICES IN INDONESIA - Hana, Jayidah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
This study aims to voice the opinions of English teachers on the existence of Indonesian English in the context of Indonesian high schools. This study employed a qualitative research method to examine the attitudes of teachers to various variations of English, especially attitudes towards their own English which is important in the World Englishes paradigm. In addition, this research can be an answer to the lack of studies on attitudes towards the variety of Indonesian and English languages. Purposive sampling was adopted in selecting participants for this study. Semi-structured interviews were used to collect qualitative data in terms of opportunities to get to know Indonesian English and their understanding of it. The findings show that the teacher acknowledges the existence of Indonesian English. This study indicates that Indonesian high school teachers declare their awareness and acceptance of Indonesian English in their high school context.